2021
DOI: 10.1161/atvbaha.120.315109
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Thymidine Phosphorylase With Tipiracil Hydrochloride Attenuates Thrombosis Without Increasing Risk of Bleeding in Mice

Abstract: Objective: Current antiplatelet medications increase the risk of bleeding, which leads to a clear clinical need in developing novel mechanism-based antiplatelet drugs. TYMP (Thymidine phosphorylase), a cytoplasm protein that is highly expressed in platelets, facilitates multiple agonist-induced platelet activation, and enhances thrombosis. Tipiracil hydrochloride (TPI), a selective TYMP inhibitor, has been approved by the Food and Drug Administration for clinical use. We tested the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 70 publications
0
40
0
Order By: Relevance
“…Based on the study from Manne et al (27), we speculate that SARS-CoV-2 can infect megakaryocytes and leads to the production of TYMP-overexpressing platelets. As mentioned above, our recent studies demonstrated that TYMP deficiency or inhibition significantly inhibited thrombosis in mice (12,13). Currently, no human study has been conducted to clarify the role of TYMP on thrombosis.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Based on the study from Manne et al (27), we speculate that SARS-CoV-2 can infect megakaryocytes and leads to the production of TYMP-overexpressing platelets. As mentioned above, our recent studies demonstrated that TYMP deficiency or inhibition significantly inhibited thrombosis in mice (12,13). Currently, no human study has been conducted to clarify the role of TYMP on thrombosis.…”
Section: Discussionmentioning
confidence: 92%
“…Administration of antiplatelet drugs to critical COVID-19 patients has achieved some clinical benefits (35). Our recent study has demonstrated that TPI is a rapidacting, safe antiplatelet medicine (13). As an auxiliary component of a novel anticancer drug, Lonsurf, TPI was approved by the FDA for clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TYMP is an intracellular protein as it lacks a peptide sequence that is required for protein secretion [12]. By using platelets isolated from human and mice, Li et al, for the first time, demonstrated that TYMP has some signaling functions, and TYMP per se, can physically bind to Src family kinases, including Lyn, Fyn, and Yes, through which it regulates platelet activation and thrombosis [13,14]. In addition to platelets, TYMP is highly expressed by circulating cells involved in the innate immune system, including monocyte, granulocytes, natural killer cells, and dendritic cells [15].…”
Section: Introductionmentioning
confidence: 99%